Graphene sheets modified with polyindole for electro-chemical detection of dopamine - Kumar A.; Prakash R. (My University, 2025)
Oxidized polyindole is coated over graphene surface by in-situ chemical oxidation method in dilute hydrochloric acid solution. Morphology of graphene modified with oxidized polyindole is investigated by scanning electron microscope. The interaction of graphene to polyindole is observed by Raman spectroscopy. The introduction of carboxylate functionality is observed in graphene due to pyrolysis. The association of this functionality with indole monomer and their interactive behaviour led to formation of uniform polyindole over graphene surface in presence of oxidizing agent. Our chemical synthesis results not only formation of uniform polymer thin layer over the graphene sheets but also enhances various properties and processibility of the graphene. Negative surface charge on the composite material is observed at acidic pH, which shows potential for accumulation of positively charged species in the solution. Further it is explored for electro-catalytic and sensing applications and shows cation permselective behavior of dopamine hydrochloride. It is demonstrated by differential pulse voltammetric technique in dopamine concentration range from 10 μM to 1 mM (in presence of 1 mM ascorbic acid). Copyright © 2014 American Scientific Publishers.